Mekanisme Pengungkapan Informasi Good Corporate Governance (Disclosure) pada Bank Syariah Indonesia - Rimi Gusliana Mais; Inayah Fatikahsari; Lilis Ainul Yaqin (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Information disclosure is a crucial element in Islamic banking governance, aimed at ensuring transparency, accountability, and the provision of relevant information to stakeholders. As the largest Islamic bank in Indonesia, Bank Syariah Indonesia (BSI) is obligated to implement information disclosure mechanisms in accordance with Islamic accounting standards, Financial Services Authority (OJK) regulations, and Sharia-based corporate governance principles. This study aims to analyze the information disclosure mechanisms implemented by BSI and their implications for public trust and institutional performance. The research employs a descriptive-analytical method with inductive reasoning. Data were obtained from various secondary sources, including scholarly journal articles, reference books, laws and regulations, Islamic accounting standards, and official reports from Bank Syariah Indonesia and relevant authorities. The results indicate that BSI’s disclosure mechanisms encompass aspects of Sharia compliance, Islamic social disclosure, and sustainability reporting. Effective implementation of disclosure is proven to enhance public trust, strengthen reputation, and support operational sustainability in accordance with Sharia principles.